Regio- and Stereoselective Synthesis of a Novel Family of Unsaturated Compounds with the S–Se Bond and Their Cyclization to 2,3-Dihydro-1,4-thiaselenines - Amosova, Svetlana V.; Filippov, Andrey S.; Potapov, Vladimir A.; Penzik, Maxim V.; Makhaeva, Nataliya A.; Albanov, Alexander I. (Synthesis, 2019)
Regio- and stereoselective ring-opening reaction of 2-bromomethyl-1,3-thiaselenole with thiols proceeded as nucleophilic attack at the selenium atom of seleniranium intermediate affording unsaturated selanyl sulfides, (Z)-CH2=CHSCH=CHSeSR, in up to 93% yield. Dithiols were involved in this reaction giving symmetrical polyunsaturated compounds with two S–Se bonds in 70–75% yields. Efficient synthesis of 2-(organylsulfanyl)-2,3-dihydro-1,4-thiaselenines in 69–96% yields was developed by the acid-catalyzed cyclization of the unsaturated selanyl sulfides. Mild reaction conditions (room temperature) and short reaction times are important features of this methodology.
Keywords: 2-bromomethyl-1,3-thiaselenole; unsaturated selanyl sulfides; seleniranium intermediates; 1,4-thiaselenines; thiols